Pengaruh Variasi Perbandingan Putaran hammer mill dan screw conveyor flash dryer Terhadap Hasil Pengeringan - Wahyudin, ilham (2016)
The purpose of this research is to know the influence of variation of comparative round hammer mill and screw conveyor flash dryer drying results and get the optimal comparison. This testing process using flash dryer by setting the comparison rounds hammer mill and screw conveyor in comparison with the 1:2, 1:2.67 and 1:3.33. With how to set magnitude of puli linking hammer mill and screw conveyor. Analisisa Results of this research show that the comparison rounds of screw conveyor and a hammer mill to comparison of incoming and outgoing flour flour. A comparison of the most optimum is 1:2,23 on comparison of round 1:3.33, with the lowest density, namely 368.42 kg/m3